The Development of Mobile Geography Virtual Laboratory for Rock and Soil Practicum Studies - Shaherani, Natasya; Putra, Alfyananda Kurnia; Soelistijo, Djoko; Yembuu, Batchuluun (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The concept of concrete lithosphere material has limitations in being verbally stimulated by the teacher, so students have difficulty understanding the material. During the learning process, lithosphere material is rarely carried out in practicum activities due to the lack of media that can involve students directly. This study aims to produce, measure feasibility, and determine the effectiveness of mobile geography virtual laboratory learning media. This research was included in R&D research by adopting a 4-D development model. The results obtained, namely the Mobile Geography Virtual Laboratory media, are feasible and effectively used in rock and soil practicum activities. The results of this research can be an innovative solution for geography learning, especially in adequately supporting the implementation of practicum activities so that students can become more active and independent.